Military-technical cooperation of Japan with foreign countries and the interests of Russia - O. G. Paramonov (Международная аналитика, 2017)
Nowadays military-technical cooperation is considered by many states as one of the effective tools for ensuring national security, as well as accomplishing a broader range of foreign policy objectives. Under a crisis of regional security environment, the Japanese government also concluded that further refusal to participate in international cooperation in the development and production of weapons begins to negatively affect its own defense capabilities. Nevertheless, Shinzo Abe-led Government’s plans to put an end to Japan’s self-isolation from external arms markets and thus strengthen relations with the United States in the military-and political fields are likely to lead to certain problems in Japan’s relations with such powerful regional actors as Russia and China.